2016
DOI: 10.1142/s2424835516500375
|View full text |Cite
|
Sign up to set email alerts
|

Surfing Behind a Boat: Quality and Reliability of Online Resources on Scaphoid Fractures

Abstract: Good quality health information is certainly available on the Internet. However, it is not possible to predict with certainty which sites are of higher quality. We suggest clinicians should have a responsibility to educate their patients regarding the unregulated nature of medical information on the internet and proactively provide patients with educational resources and thus help them make smart and informed decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Furthermore, the information presented on the websites was categorized as etiology, prevention, and/or treatment of dental caries. The presence or absence of these contents was graphically represented by the software Genesis (version 1.7.7, Graz, Austria), characterizing the identity of each website [ 45 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the information presented on the websites was categorized as etiology, prevention, and/or treatment of dental caries. The presence or absence of these contents was graphically represented by the software Genesis (version 1.7.7, Graz, Austria), characterizing the identity of each website [ 45 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…The application of the DISCERN showed a general low trustworthiness for the websites on acute myocardial infarction and stroke showed (54.2%) [58], and caesarean section reports (DISCERN=43.6) [59]. Regarding the JAMA scores, our results are consistent with previous works [44,49,63]; however, there is not dental cariesrelated evidence considering this method.…”
Section: Discussionsupporting
confidence: 85%
“…(1), prevention (2), and/or treatment (3) of dental caries, which determined the websites' identities [49]. The ID of each website was graphically represented by the software Genesis (version 1.7.7, Graz, Austria) [50] The Assessment of Quality of Websites Two independent examiners (PEAA and MMC) evaluated the quality of websites using two different instruments, the DISCERN questionnaire [33,51] and the Journal of the American Medical Association (JAMA) benchmark criteria [52].…”
Section: Selection Of Websitesmentioning
confidence: 99%
“…independently conducted simultaneous, comprehensive searches of the top 3 Internet search engines—Google, Yahoo, and Bing—using Google Chrome (the most commonly used browser) to collect Internet-based educational resources about HF medications. 7 , 9 , 11 , 15 , 16 Search queries included the following: (i) “Heart failure medication patient information”; (ii) “Heart failure medications patient information”; (iii) “Heart failure medication patient handout”; (iv) “Heart failure medications patient handout”; (v) “Heart failure drugs patient information”; and (vi) “Heart failure drugs patient handout”. The search queries used were developed through discussion and collaboration between the researchers, with the goal of replicating search terms that patients looking for this information might use (ie, more general, broad terms, in lay language).…”
Section: Methodsmentioning
confidence: 99%
“…Emerging evidence documents the suboptimal quality and readability of patient educational resources. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 For instance, a 2014 review assessed the quality of available patient educational resources on left ventricular assist devices, for patients with advanced HF, using the Flesch-Kincaid Grade Level score, the Fry algorithm, and a modified version of the International Patient Decision Aid Standards. 8 This study found that most educational resources available online that address left ventricular assist devices are of suboptimal quality.…”
mentioning
confidence: 99%